Transcriptomic atlas for hypoxia and following re-oxygenation in Ancherythroculter nigrocauda heart and brain tissues: insights into gene expression, alternative splicing, and signaling pathways - Chen, Jian; Hu, Zhen; Li, Pei; Wang, Guiying; Wei, Huijie; Li, Qing; Fu, Beide; Sun, Yanhong (Frontiers in Genetics, 2024)
Hypoxia is a mounting problem that affects the world's freshwaters, with severe consequence for many species, including death and large economical loss. The hypoxia problem has increased recently due to the combined effects of water eutrophication and global warming. In this study, we investigated the transcriptome atlas for the bony fish Ancherythroculter nigrocauda under hypoxia for 1.5, 3, and 4.5 hours and its recovery to normal oxygen levels in heart and brain tissues. We sequenced 21 samples for brain and heart tissues (a total of 42 samples) plus three control samples and obtained an average of 32.40 million raw reads per sample, and 95.24% mapping rate of the filtered clean reads. This robust transcriptome dataset facilitated the discovery of 52,428 new transcripts and 6,609 novel genes. In the heart tissue, the KEGG enrichment analysis showed that genes linked to the Vascular smooth muscle contraction and MAPK and VEGF signaling pathways were notably altered under hypoxia. Re-oxygenation introduced changes in genes associated with abiotic stimulus response and stress regulation. In the heart tissue, weighted gene co-expression network analysis pinpointed a module enriched in insulin receptor pathways that was correlated with hypoxia. Conversely, in the brain tissue, the response to hypoxia was characterized by alterations in the PPAR signaling pathway, and re-oxygenation influenced the mTOR and FoxO signaling pathways. Alternative splicing analysis identified an average of 27,226 and 28,290 events in the heart and brain tissues, respectively, with differential events between control and hypoxia-stressed groups. This study offers a holistic view of transcriptomic adaptations in A. nigrocauda heart and brain tissues under oxygen stress and emphasizes the role of gene expression and alternative splicing in the response mechanisms.